Clostridium difficile infection: clinico-epidemiological perspective. - SYUHADA N; AZIMATUN NA; ALFIZAH H; TZAR, MN; RAMLIZA R1 (Penerbit UKM, 2013)
Clostridium difficile infection (CDI) causes mild to severe diarrhoea and pseudomembranous colitis in patients who had prior antibiotic exposure. Despite CDI being prevalent worldwide, its epidemiological data is scanty in Malaysia. This study aimed to determine the prevalence and incidence of CDI at Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Stool specimens from 147-suspected CDI patients were obtained from 1 November 2011 until 31 October 2012. The presence of C. difficile toxin A and/or B were detected using a commercial immunochromatographic kit (Wampole™ Tox A/B Quik Chek). Surveillance data was collected from patients’ medical records to establish the demographic and clinical characteristics. The overall prevalence and incidence of CDI in UKMMC was 6.1% and 5.2 cases per 10 000 patient-days, respectively. Among nine CDI patients, 77.8% were males and 55.6% were Chinese. CDI was most common in medical wards (88.9%). The median age was 60 years and the median length of hospital stay was 13 days. Majority (88.9%) of CDI patients received antibiotics eight weeks prior to CDI. Penicillin-beta-lactamase inhibitors were the most common antecedent antibiotics. Five (55.6%) CDI patients received acid suppressant medications. The in-hospital mortality rate was 22.2%. In conclusion, the prevalence and incidence of CDI at UKMMC is relatively low and occurs sporadically.